Development of Articulate Storyline Media on Biodiversity Content Featuring Tropical Rainforests to Enhance Students’ Critical and Creative Thinking Skills - Alfisyahrani; Makrina Tindangen; Krishna Purnawan Candra (Jurnal Penelitian Pendidikan IPA, 2025)
This research aimed to develop and assess the practicality and effectiveness of the Articulate Storyline Media (ASM) for teaching biodiversity, focusing on tropical rainforest content, for 10th-class students. The study applied the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Data collected were student responses for practicality and test results in assessing critical and creative thinking skills. Results showed that the interactive media achieved a practicality rating of 74% and 100% for the students and teacher, respectively. The effectiveness of the ASM in enhancing the creative thinking skills in the experimental class was significantly (p<0.000) higher, i.e., 89%, compared to 65% in the control group. These findings indicate that the Articulate Storyline media on biodiversity content efficiently and effectively enhances 10th-class students’ critical and creative thinking skills.